2015
DOI: 10.1074/jbc.m115.664037
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma-derived Macrophage Colony-stimulating Factor (MCSF) Induces Microglial Release of Insulin-like Growth Factor-binding Protein 1 (IGFBP1) to Promote Angiogenesis

Abstract: Background: Glioblastoma is highly aggressive and incurable by current treatment modalities. Results: MCSF is regulated by the SYK-PI3K-NFB pathway in glioma and induces secretion of IGFBP1 from microglia to promote angiogenesis. Conclusion: Microglial IGFBP1 is a key mediator of MCSF-induced angiogenesis. Significance: IGFBP1 is a potential target for glioblastoma therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 67 publications
1
59
0
3
Order By: Relevance
“…IL-6 is able to promote epithelial-mesenchymal transition of cancer cells, which is typically operative in high-grade gliomas. 51 Other paracrine factors that influence the sprouting process include TAM-derived WNT7b and M-CSF in breast cancer and glioma, which can activate the canonical WNT/β-catenin and insulin-like growth factor binding protein pathways, respectively, in endothelial cells, thereby increasing the expression of VEGFA and contributing to vascular sprouting 52,53 (Fig. 2C).…”
Section: Neurooncologymentioning
confidence: 99%
“…IL-6 is able to promote epithelial-mesenchymal transition of cancer cells, which is typically operative in high-grade gliomas. 51 Other paracrine factors that influence the sprouting process include TAM-derived WNT7b and M-CSF in breast cancer and glioma, which can activate the canonical WNT/β-catenin and insulin-like growth factor binding protein pathways, respectively, in endothelial cells, thereby increasing the expression of VEGFA and contributing to vascular sprouting 52,53 (Fig. 2C).…”
Section: Neurooncologymentioning
confidence: 99%
“…При ангиогенных заболеваниях, к которым от-носится опухолевый рост, имеет место патологический ангиогенез, в развитии которого особую роль играют фактор роста эндотелия сосудов (VEGF), фактор роста фибробластов (FGF), трансформирующие факторы роста α и ß, которые известны как факторы «запуска» ангиогенеза, и другие факторы [5,6]. Расшифровка важных механизмов ангиогенеза в физиологическом и патологическом состоянии осталась предметом по-вышенного интереса в течение последних 30 лет.…”
Section: Play a Special Role In Its Development Evaluation Of The Imunclassified
“…Авторы показали, что в злокачественных опухолях уровень этого фактора роста был значимо выше, чем в менин-гиомах. Увеличение уровня VEGF в ткани глиобластом показано многочисленными исследованиями [5][6][7][8]. Известно, что VEGF экспрессируются преимуществен-но опухолевыми клетками и в меньшей степени -клетками окружающих тканей глиом [15].…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…Th us, Kim et al (2016) have shown that IGFBP1 and ALDH1A1 are diff erentially overexpressed in the colorectal cancer liver metastasis and may play a dual role, functioning as both tumor suppressors and metastasis promoters in colorectal cancer. Furthermore, there are data that glioblastoma-derived MCSF (macrophage colony-stimulating factor) induces microglial release of IGFBP1 to promote angiogenesis (Nijaguna et al 2015). IGFBP2 is highly up-regulated in glioblastoma tissues.…”
mentioning
confidence: 99%